ANALISIS TEORI PERMAINAN DENGAN RANTAI MARKOV UNTUK PENENTUAN STRATEGI OPTIMAL DAN PERPINDAHAN PENGGUNA PADA OJEK ONLINE - Arma, Abdul; Wasono; Amijaya, Fidia Deny Tisna (Universitas Insan Budi Utomo, 2026)
The development of transportation services in Indonesia has led to increasing competition among online motorcycle taxi service providers, particularly between Gojek and Grab. This competition is not limited to pricing aspects but also includes promotional offers and vouchers, ease of application use, service completeness, payment methods, and the quality of driver services. These conditions potentially affect user loyalty and encourage customer switching behavior. This study aims to determine the optimal competitive strategies between Gojek and Grab and to analyze user switching patterns. The data used in this study are primary data obtained through questionnaires distributed to students of Mulawarman University who use online motorcycle taxi services. Game theory is applied to model competition between two players in a zero-sum game framework, where each company acts rationally in selecting strategies to maximize relative profits against its competitor. The payoff matrix is constructed based on questionnaire results and analyzed using pure strategies to determine the optimal strategy through the saddle point value. Markov chains are employed to analyze user switching behavior by modeling transition probabilities between states, namely Gojek and Grab, and to estimate the distribution of users in future periods until reaching a steady-state condition. The results indicate that the optimal strategy based on game theory, with Gojek as the row player and Grab as the column player, is the promotional and voucher strategy with a saddle point value of −10. Markov chain analysis shows that the probability of users switching from Gojek to Grab is 0,14 while the probability of switching from Grab to Gojek is 0.04. The steady-state condition is achieved in the 28th period, with user probabilities of 0,223 for Gojek and 0,777 for Grab. These findings indicate that, in the long run, students of Mulawarman University tend to switch from Gojek to Grab.